A dual‐process exploration of binge drinking: Evidence through behavioral and electrophysiological findings. (29th October 2018) - Lannoy, Séverine; Dormal, Valérie; Billieux, Joël; Brion, Mélanie; D'Hondt, Fabien; Maurage, Pierre
Abstract: The dual‐process model, describing addictive disorders as resulting from an imbalance between increased automatic approach behaviors towards the substance and reduced abilities to control these behaviors, constitutes a sound theoretical framework to understand alcohol‐use disorders. The present study aimed at exploring this imbalance at behavioral and cerebral levels in binge drinking, a pattern of excessive alcohol consumption frequently observed in youth, by assessing both reflective control abilities and automatic processing of alcohol‐related stimuli. For this purpose, 25 binge drinkers and 25 comparison participants performed a Go/No‐Go task during electrophysiological recording. Inhibition abilities were investigated during explicit (ie, distinguishing alcoholic versus nonalcoholic drinks) and implicit (ie, distinguishing sparkling versus nonsparkling drinks, independently of their alcohol content) processing of beverage cues. Binge drinkers presented poorer inhibition for the explicit processing of beverage cues, as well as reduced N200 amplitude for the specific processing of alcohol‐related stimuli. As a whole, these findings indicated inhibition impairments in binge drinkers, particularly for alcohol cues processing and at the attentional stage of the cognitive stream. In line with the dual‐process model, these results support that binge drinking is already characterized by an underactivation of the reflective system combined with an overactivation of the automatic system. Results also underlined the influence of explicit processing compared with implicit ones. At the clinical level, our findings reinforce the need to develop intervention methods focusing on the inhibition of approach behaviors towards alcohol‐related stimuli. Abstract : We explored the electrophysiological correlates of explicit and implicit processing of alcohol‐related stimuli among 25 binge drinkers and 25 matched comparison participants. While no group differences were observed for the implicit condition, reduced inhibition abilities were observed among binge drinkers for the explicit condition, together with reduced N200 amplitude during the processing of alcohol‐related stimuli. Binge drinking is associated with inhibition impairments, particularly when confronted with alcohol‐related stimuli, and this impairment appears related to an impaired attentional step of the cognitive stream.